Emerging Water Pollutants: Concerns and Remediation Technologies 2022
DOI: 10.2174/97897815040739122010014
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Processes for Removal of Emerging Water Pollutants

Abstract: An unprecedented increase in urbanization and industrialization ignited by an upsurge in the development of consumer goods. This has been steadily destroying the environmental balance and ecosystem and diminishing the water quality. Inevitably, we are facing one of the biggest challenges of the time, which needs to be resolved with proper remediation strategies to provide clean water as one of the essential components for human beings and agriculture, livestock, and several industrial survivals. With the growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 161 publications
0
1
0
Order By: Relevance
“…2 They possess unique physiochemical properties like stable photoluminescence (PL), versatile surface chemistry, excellent hydrophilicity, biocompatibility, 3 low toxicity, excitation wavelength-dependent emission, and eco-friendly nature. 4 CQDs can be used in a plethora of applications like sensing, 5 solar cells, bio-imaging, bio-electrochemistry, 6 nanomedicine, 7 and photocatalysis. 8 A thorough review of the available literature found that organic compounds and natural precursors (biomass and biowaste) were employed to synthesize CQDs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2 They possess unique physiochemical properties like stable photoluminescence (PL), versatile surface chemistry, excellent hydrophilicity, biocompatibility, 3 low toxicity, excitation wavelength-dependent emission, and eco-friendly nature. 4 CQDs can be used in a plethora of applications like sensing, 5 solar cells, bio-imaging, bio-electrochemistry, 6 nanomedicine, 7 and photocatalysis. 8 A thorough review of the available literature found that organic compounds and natural precursors (biomass and biowaste) were employed to synthesize CQDs.…”
Section: ■ Introductionmentioning
confidence: 99%